2012
DOI: 10.1080/10934529.2012.673306
|View full text |Cite
|
Sign up to set email alerts
|

Improved urban stormwater treatment and pollutant removal pathways in amended wet detention ponds

Abstract: Dissolved and colloidal bound pollutants are generally poorly removed from stormwater in wet detention ponds. These fractions are, however, the most bio-available, and therefore three wet detention ponds were amended with planted sand filters, sorption filters and addition of precipitation chemicals to enhance the removal of dissolved pollutants and pollutants associated with fine particles and colloids. The three systems treated runoff from industrial, residential and combined (residential and highway) catchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 31 publications
4
11
1
Order By: Relevance
“…The concentrations of commonly-monitored trace elements (i.e. Cd, Cr, Cu, Ni, Pb, Zn) were detected within the same order of magnitude as those observed in several previous international and national studies (Jang et al 2010;Blecken et al 2012;Istenič et al 2012;Egemose et al 2015;Frost et al 2015;Sharley et al 2017;Crane 2019;Sun et al 2019), but lower maximum concentration values were obtained here compared to those found in ponds within industrial areas (Sharley et al 2017). Blecken et al (2012) also detected six-fold higher Cr concentrations in sediment close to stormwater outlets, while Jang et al (2010) observed four-fold higher maximum values in road residues.…”
Section: Concentrations Of Elements In Sedimentsupporting
confidence: 85%
“…The concentrations of commonly-monitored trace elements (i.e. Cd, Cr, Cu, Ni, Pb, Zn) were detected within the same order of magnitude as those observed in several previous international and national studies (Jang et al 2010;Blecken et al 2012;Istenič et al 2012;Egemose et al 2015;Frost et al 2015;Sharley et al 2017;Crane 2019;Sun et al 2019), but lower maximum concentration values were obtained here compared to those found in ponds within industrial areas (Sharley et al 2017). Blecken et al (2012) also detected six-fold higher Cr concentrations in sediment close to stormwater outlets, while Jang et al (2010) observed four-fold higher maximum values in road residues.…”
Section: Concentrations Of Elements In Sedimentsupporting
confidence: 85%
“…Degradation is more associated with the activity of microorganisms present in the sediment-water system [18,19], where redox potential and oxygen condition are main factors [20][21][22][23]. Studies have already shown that stormwater retention ponds can reduce pollutants including polycyclic aromatic hydrocarbons (PAHs), heavy metals and biocides by processes like adsorption, sedimentation and degradation [24][25][26]. However, less is known about the fate of pharmaceuticals in such ponds, especially the removal mechanisms and the main factors that govern removal rates.…”
Section: Introductionmentioning
confidence: 99%
“…A targeted, less costly and less disruptive plan to control the downstream transfer of chlordane from sources is suggested by this research and others where up to 94% of TPAH in Lower Paint Branch was retained by an experimental urban stormwater bioretention facility (DiBlasi et al ). Holding ponds and cisterns have been examined as intercepts for TSS contaminants (Somes et al ; Istenic et al ). Immobilization of pond‐trapped contaminants by in situ toxics management using C has been reported (Ghosh et al ).…”
Section: Discussionmentioning
confidence: 99%